Cholera outbreak in diyala province - Hashim Ibrahim , Arkan; Abbas , Rafal; hazem, Ali (Diyala Journal of Medicine, 2024)
Background: Vibrio cholerae is a primary cause of severe dehydrating diarrhea and remains a serious public health problem in low- and middle-income countries (LMICs) with insufficient water, sanitation, and hygiene. Cholera remains a public health threat the worldwide, mainly in countries with poor access to safe water and sanitation facilities. According to estimates, there are 21,000–143,000 deaths and 1.3–4 million cases of cholera annual. Objective: This study aims to carry out an analysis of the available information on cholera outbreaks in Diyala province, 2022. Patients and Methods: A descriptive study conducted in the department of public health using the data of cases reported from eight sectors in province. The data was collected from the surveillance unit, communicable control division of the public health department in Diyala province, IRAQ in 2022. Results: The total number of confirmed cases of cholera was (n = 139), female (72) 52 % and male (67) 48%, death reported for two of these cases. According to the date of onset, the registration of cases began from July 19 to October 25, 2022. However, the case fatality ratio (CFR) was 1.4%, while the attack rate in the governorate is 7.6 per 100,000 populations during 2022, the highest attack rate in Khanaqin district was (77 cases) 46, while the lowest attack rate in Baldruze, Al-Mansuria, and Al-Khalis districts was (1 case) 0.3,0.6, and 0.8 respectively. The age mean of patients was (38.7 ± 17.14 years) and the occurrence of the disease is more incidence in the age group 30-44 and females more than males. Conclusion: Occurrence Cholera outbreak during year 2022 without confirmed cases recorded since 2015 and the occurrence of cholera cases in governorate is greater during the months of August and September and most of the cases were from Khanaqin district.